Transit Route Design Solved with Wireless Data Collection Algorithms. Issue 1 (January 2014) - Rey, David; Almi'ani, Khaled; Viglas, Anastasios; Libman, Lavy; Waller, S. Travis
The transit route network design problem and its variants, aiming for economically viable and efficient transit routes in urban areas, has been attracting many contributions in recent years and continues to be an active research field. This activity is mainly caused by the intractability of the underlying optimization problems in large-scale transportation networks, generally leading to the use of heuristic schemes to build good practical solutions. A relationship between the transit route network design problem and the problem of data collection in wireless sensor networks is presented, and an innovative solution approach is proposed based on a recently proposed algorithm in that domain. The original solution algorithm is adapted to urban transportation networks and tests are carried out on large-scale data sets on a single-route variant of the transit route network design problem. The results obtained show that the solution approach can be efficiently tuned to meet specific route design objectives and provide balanced solutions.